Penerapan Teknik Mozaik Pada Benda 3 Dimensi Berbahan Dasar Sampah Plastik Siswa Kelas III SDN 18 Kota Bengkulu - Amanda, Aura Muerly; Anggraini, Dwi; Agusdianita, Neza (JURIDIKDAS, 2024)
This research aims to describe the process of making mosaic works on 3-dimensional objects using plastic waste as basic materials and the resulting mosaic work as a work of fine art. This type of research is qualitative research with descriptive methods. The research subjects were 29 class III students at SD Negeri 18 Bengkulu City. The instrument in this research was the researcher himself using observation sheets, interview sheets and documentation. The data collection techniques used were observation, interviews and documentation. Data analysis is carried out by collecting data, reducing data, presenting data and drawing conclusions. This research data validity technique uses triangulation and member checking. The results of this research are (1) The process of making a work is carried out in 4 stages, namely the stage of preparing the motif design, the stage of preparing tools and materials, the stage of sticking, and the stage of final completion. The work is made in the form of a mosaic on a 3-dimensional object, namely a pencil holder made of cardboard. Making mosaics using plastic waste as basic materials. In the process of making works, it was found that not having tools and materials ready could affect students' performance, where in group 4, who did not bring materials, namely plastic waste, group 4 had to look for plastic waste first around the school, which took more time and made the time for making their work shorter.